THE ROLE OF FINANCIAL TECHNOLOGY INNOVATION (FINTECH) IN IMPROVING THE OPERATIONAL EFFICIENCY OF MSMES IN BINTAN REGENCY - Rakesh Sitepu; Sri Fitria Jayusman; Sari Wulandari; Debbi Chyntia Ovami; Serli Yuli Marlina (CV. Radja Publika, 2026)
After the Covid-19 Pandemic, Indonesia, especially Bintan Regency, is faced with the challenge of improving the operational efficiency of MSMEs (Micro, Small and Medium Enterprises) in various zones, especially in financial management. This research aims to study the position or role of financial technology innovation in improving the operational efficiency of MSMEs in Bintan Regency. The use of technology can share many conveniences in every business activity. Financial technology (Fintech) is one of the drivers of business growth at this time. The research method used is using a qualitative descriptive approach. Qualitative descriptive analysis is research that correctly and accurately describes the process or event that is happening as the object of research. The information or data is then analyzed to get results. The findings of the study prove that the use of Fintech such as digital payment systems, expense tracing, and financial information analysis can significantly increase the operational efficiency of MSMEs in Bintan Regency. This study shares a better description of Fintech innovations that can be applied efficiently and effectively to improve financial and operational performance in Bintan Regency. In short, financial technology innovation has great ability to improve operational efficiency with synergistic cooperation between stakeholders to be able to improve digital skills, as well as infrastructure investment.